Current Development in Synthesis and Characterization of Nickel Ferrite Nanoparticle. (2017) - Gupta, Nitish; Jain, Pranat; Rana, Ravindra; Shrivastava, Sanjay
Abstract: This paper presents a comprehensive review on the synthesis and characterization techniques of ferrospinel nickel ferrite. AFe2 O4 ferrospinels are a group of technologically important material due to their high electrical resistivity, sufficiently low dielectric loss over a wide range of frequency, high corrosion resistance, and thermodynamic stability. Among the ferrospinels, the inverse spinel is particularly interesting due to its high saturation magnetization and unique magnetic structure. Nickel ferrite with an inverse spinel structure shows ferromagnetism. This ferromagnetism originated from magnetic moment of anti parallel spins between Fe 3+ ions at tetrahedral sides and Ni 2+ ions at octahedral sides. Synthesis approaches of nickel ferrite include co-precipitation, combustion method, sol–gel process, spray pyrolysis, micro emulsion technique, pulsed wire discharge, soft mechanochemical route, chemical vapor deposition and hydrothermal process. Different techniques used to characterize nickel ferrite nanoparticles are, thermogrametric analysis (TGA), X ray diffraction(XRD), X-ray Photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), and transmission electron microscopy (TEM), two-point probe electrical resistivity technique and vibrating sample magnetometer (VSM). Comprehensive understanding of these synthesis and characterization techniques are a vital component to obtain nanoparticles of desired properties and therefore, the aim of this paper is to review current developments in the synthesis and characterization techniques of nickel ferrite nanoparticles